Description of the bromeliad-dwelling final instar larva of Leptagrion andromache Hagen in Selys (Zygoptera: Coenagrionidae) - Muzón, Javier; Muñoz, Soledad Weigel; Campos, Raúl (Zootaxa, 2009)
The Neotropical genus Leptagrion Selys is composed by 16 species, mainly distributed in northern and central South America (Costa & Garrison 2001; De Marmels & Garrison 2005; Lencioni 2006). Only phytotelmic habitats were recorded for its larvae, exclusively in bromeliads, e.g., Vriesia, Neoregelia, Quesnelia, Portea, Bilbergia, Canistrum, Aechmea (Santos 1966, 1968, 1978, 1979; Lounibos et al. 1987; Corbet 1999). However, no final stage larva of any species of Leptagrion has been described to date. De Marmels (1985) described that of L. fernandezianum Rácenis, but this species was transferred to the newly erected and related genus Bromeliagrion De Marmels in De Marmels & Garrison (De Marmels & Garrison 2005). In addition, Torreias et al. (2008) described the final instar larva of B. rehni Garrison from Guzmania bromeliads. Leptagrion andromache Hagen in Selys belongs to the porrectum species group and was previously recorded from Brazil (Espirito Santo) (Costa & Garrison 2001; Lencioni 2006). In this paper we describe the final instar larva of L. andromache based on reared specimens of both sexes collected in Misiones province, Argentina and we compare them with that of B. fernandezianum and B. rehni.